2000
DOI: 10.1044/jslhr.4303.706
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Voice Analysis by Means of the Hoarseness Diagram

Abstract: The hoarseness diagram (Michaelis, Fröhlich, & Strube, 1998a) has been proposed as a new approach to describe different acoustic properties of voices. To test its performance in the analysis of pathologically disturbed and normal voices five requirements are suggested that should be met by any acoustic voice-analysis protocol to be used in voice research and clinical practice. The hoarseness diagram is then tested with regard to these requirements. Individual voices are found to show a satisfactory localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
18

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(99 citation statements)
references
References 26 publications
1
80
0
18
Order By: Relevance
“…Acoustic analysis employs computerbased techniques to measure the properties of the acoustic signal-whether from a vowel or connected speech-providing more objective information regarding the voice signal compared to the auditoryperceptual analysis, as it produces quantitative data in the voice assessment process [9][10][11][12][13] .…”
Section: Análise Acústica De Vozes Infantis: Contribuições Do Diagrammentioning
confidence: 99%
See 2 more Smart Citations
“…Acoustic analysis employs computerbased techniques to measure the properties of the acoustic signal-whether from a vowel or connected speech-providing more objective information regarding the voice signal compared to the auditoryperceptual analysis, as it produces quantitative data in the voice assessment process [9][10][11][12][13] .…”
Section: Análise Acústica De Vozes Infantis: Contribuições Do Diagrammentioning
confidence: 99%
“…In view of this, some studies [8][9][10][11][12] have indicated that a voice assessment should use a combination of several acoustic measures of perturbation and noise, so that each individual utterance is quantified by a set of attributes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was possible to verify that the totality of vocal samples from the partial laryngectomy group were distributed out of the normality quadrant. Authors point that altered voices are located out of the lower left quadrant, in which are located adapted voices 10,13,[20][21][22] . The statistical analysis revealed that there was no significant difference in the comparison of the distribution of both groups.…”
Section: Discussionmentioning
confidence: 99%
“…The diagram is based in four acoustic measures: three of them related to irregularity of the sound signal -jitter, shimmer and their correlation; the fourth one is related to the noise component, named glottal to noise excitation ratio -GNE [13][14][15] . The differential of this diagram is that it is able to assess very deviant voices, besides showing differences between dysphonic groups with different phonatory mechanisms and it allows monitoring of vocal quality 10,[13][14][15][16][17] . The GNE is the acoustic measure that calculates the noise produced by the oscillation of vocal chords.…”
Section: Methodsmentioning
confidence: 99%